2014
DOI: 10.5588/ijtld.13.0335
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of depressive state among pulmonary tuberculosis patients in Manila, The Philippines

Abstract: S E T T I N G :Both depression and tuberculosis (TB) are global public health problems that have a substantial impact on human health. However, depressive state among TB patients has not been well investigated in the Philippines. O B J E C T I V E : To assess depressive state among pulmonary tuberculosis (PTB) patients and to identify factors associated with depressive state in Manila, the Philippines. D E S I G N : A cross-sectional survey of PTB patients was conducted at 10 public health centres and two nong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
52
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 19 publications
14
52
2
3
Order By: Relevance
“…Frequency of depression observed in this study (87.5%) was much greater as compared with the prevalence in the general population of Pakistan (45.98%) [22]. This study finding is much greater as compared with 11% found by Aghanwa and colleague in Nigeria [23], 19% found in Turkey [24], 49% found by Natani and colleagues in India [25] and comparable with 80% found in hospitalized patients in Pakistan [26]. Compared with the previous reports in other countries, prevalence of depressive state among MDR-TB patients was relatively higher in the present study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Frequency of depression observed in this study (87.5%) was much greater as compared with the prevalence in the general population of Pakistan (45.98%) [22]. This study finding is much greater as compared with 11% found by Aghanwa and colleague in Nigeria [23], 19% found in Turkey [24], 49% found by Natani and colleagues in India [25] and comparable with 80% found in hospitalized patients in Pakistan [26]. Compared with the previous reports in other countries, prevalence of depressive state among MDR-TB patients was relatively higher in the present study.…”
Section: Discussionsupporting
confidence: 58%
“…Female patients with MDR-TB in developing countries become lonely, underestimated and socially stigmatized with consequent depression [29]. Gender depression is also associated with younger age [26]. In the present study all MDR-TB patient with age lower than 30 years, had experienced more episode of depression as compared to older age patients.…”
Section: Discussionsupporting
confidence: 46%
“…In a study conducted in the Philippines, a prevalence rate of 16.8% found patients with TB as being in a depressive state. However, the rates were lower than present studies [6]. A systematic review showed a greater frequency in relation to the common and lower in relation to depression [54].…”
Section: Impact On Lifecontrasting
confidence: 41%
“…The association of depression to tuberculosis also has been investigated in other countries. In Manila, Philippines, 17% of 561 patients under directly observed treatment in 12 public services suffered from depression [6]. In a tertiary care hospital, in India, 84% out of the 147 patients presented depressive symptoms over a period of 15 months of observation [7].…”
Section: Introductionmentioning
confidence: 99%
“…A mere diagnosis of these chronic medical diseases can pose serious psychological trauma for the sufferer, giving rise to varied psychiatric symptoms and comorbidities [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The situation has greatly worsened with the recent surge in co-infection of tuberculosis with HIV infection [27][28][29].…”
Section: Introductionmentioning
confidence: 99%